1990
DOI: 10.1007/bf01939930
|View full text |Cite
|
Sign up to set email alerts
|

Muscle lipofuscin content and satellite cell volume is increased after high altitude exposure in humans

Abstract: Muscle ultrastructural changes during a typical expedition to the Himalayas were analyzed by taking muscle biopsies from seven climbers before and after their sojourn at high altitude (over 5000 m for 8 weeks). M. vastus lateralis samples were analyzed morphometrically from electron micrographs. A quantitative evaluation was made of lipofuscin, satellite cells and myonuclei. Significant increases of the volume densities of lipofuscin (+ 235%) and satellite cells (+ 215%) were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…We found the volume fraction of lipofuscin inclusions ( Fig. 2) to be significantly increased by over 2-fold after return from the expeditions (Martinelli et al 1990). Lipofuscin is believed to be a degradation product of mitochondria, prevailing under conditions of increased oxygen radical formation (Brunk & Terman, 2002).…”
Section: Long-term Hypoxia On Mountaineering Expeditionsmentioning
confidence: 76%
See 1 more Smart Citation
“…We found the volume fraction of lipofuscin inclusions ( Fig. 2) to be significantly increased by over 2-fold after return from the expeditions (Martinelli et al 1990). Lipofuscin is believed to be a degradation product of mitochondria, prevailing under conditions of increased oxygen radical formation (Brunk & Terman, 2002).…”
Section: Long-term Hypoxia On Mountaineering Expeditionsmentioning
confidence: 76%
“…Moreover, ROS-activated signalling events involving MAPK and PI-3 K/Akt have been implied in the modulation of the transcriptional activity of HIF-1a (Richard et al 1999;Minet et al 2001). Last but not least, ROS production potentially could explain the accumulation of the by-products of radical metabolism, such as the breakdown product of mitochondria, lipofuscin (Brunk & Terman, 2002), in low-landers after having spent weeks at high altitude (Martinelli et al 1990). …”
Section: Ros Production During Hypoxia: Are Mitochondria Oxygen Sensors?mentioning
confidence: 99%
“…Two studies have reported cumulative oxidative stress and damage in resting muscle of healthy subjects exposed to an oxygen deficient environment. Martinelli and co-workers 12 reported a threefold increase in basal levels of lipofuscin, a pigment marker of cumulative oxidative stress, in the vastus lateralis of climbers after a high altitude expedition over 5000 m for 8 weeks. More recently, Lundby and colleagues 13 reported an increase in resting muscle oxidative DNA damage in seven healthy subjects after 2 weeks at 4100 m. Chronic hypoxaemia, a common physiopathological consequence of COPD, is associated with poor tolerance of peripheral muscle exercise.…”
mentioning
confidence: 99%
“…Mitochondria play a central role in all these processes due to their active implication in energy production and the regulation of cell death. This is supported by the selective accumulation of the mitochondrial breakdown product lipofuscin concomitantly with reduced mitochondrial volume density in Caucasian mountaineers after altitude exposure (Martinelli et al, 1990;Gelfi et al, 2004). These alterations resemble mitochondrial autophagy, which removes damaged mitochondria and serves to control muscle fiber atrophy that originates from local fiber death induced by cytochome c release from injured mitochondria (Decker and Wildenthal, 1980;Terman et al, 2004;Gustafsson and Gottlieb, 2008).…”
Section: Zones Of Adaptation To Exercise In Hypoxiamentioning
confidence: 98%